Description of the nymph of Miroculis (Miroculis) eldorado Gama-Neto & Hamada, 2014 (Leptophlebiidae: Ephemeroptera) from Roraima, northern Brazil - Boldrini, Rafael; Lima, Lucas Ramos Costa; Ottoni-Boldrini, Bianca Maira De Paiva (Zootaxa, 2018)
The genus Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) is represented by 23 species: two of them aredescribed based solely on nymphs, 10 based solely on male adults, and three based on nymphs and adults  (Domínguez et al., 2006; Gama-Neto & Hamada, 2013, 2014; Raimundi et al., 2017). Currently, the genus is represented by six species in Roraima State, Brazil, all are described as adults but only one of them has the nymphal stage described (Gama-Neto & Hamada, 2013, 2014; Gama-Neto et al., 2018; Raimundi et al., 2017).